Hybrid zones: windows on climate change. (July 2015) - Taylor, Scott A.; Larson, Erica L.; Harrison, Richard G.
Highlights Hybrid zones can be monitored to understand changes in species distributions. Hybrid zones can be monitored to document adaptive introgression. Citizen science can help us monitor hybrid zones. Hybrid zones can act as windows on climate change.